Understanding Attachment to Place in the context of the 2021 Tajogaite eruption crisis and recovery, La Palma - Rice, Rosie; Oppenheimer, Clive (Volcanica, 2025)
Previous research on place attachment in disaster contexts has focused on its influence on risk perception, evacuation, relo- cation, and its re-establishment post-disaster. However, consideration of place attachment in risk management has hitherto been little studied. The 2021 eruption of Volcán de Tajogaite, La Palma, significantly damaged urban areas and some residents still wait to be rehoused or allowed to return to their homes. Here we show that: (i) place attachment, particularly to the home, was largely neglected during the emergency yet strongly influenced resident experiences, and (ii) attachment to place is being re-established amongst the communities in temporary housing, encouraging people to stay on the island. Drawing on these findings, we make recommendations for ‘place-based’ emergency management with broad relevance to volcanic islands. Resumen Los estudios anteriores sobre el apego al lugar y los desastres se han centrado en su influencia en la percepción del riesgo,la evacuación, la reubicación y su restablecimiento después de un desastre. La erupción del Volcán de Tajogaite en La Palmaen 2021 dañó gravemente las áreas urbanas, y muchos residentes aún esperan ser reubicados o regresar a sus hogares. Aquídemuestramos que: (i) si bien el apego al lugar no fue considerado durante las evacuaciones de emergencia, este tuvo unagran influencia en las experiencias de los residentes, y (ii) el apego al lugar se está reestableciendo entre las comunidades enviviendas temporales, lo que anima a las personas a permanecer en la isla. Con base en estos hallazgos, propongamos unagestión de riesgos "basada en el lugarçon amplia relevancia para las islas volcánicas.